An evaluation of preventive sensor technology for dementia care. (February 2013) - Nijhof, Nienke; Van Gemert-Pijnen, Lisette Jewc; Woolrych, Ryan; Sixsmith, Andrew
We evaluated a commercially-available monitoring system for older people with dementia living at home. The system was designed to detect problems before they require crisis intervention. Fourteen clients from two healthcare organisations in the Netherlands used the system over a 9-month period. The formal and informal caregivers were interviewed, project group meetings were observed, nurse diaries were analysed and a cost analysis performed. Clients and informal caregivers reported enhanced feelings of safety and security as a result of having the system installed in the home. The system appeared to reduce the burden of care on the informal caregiver and had the potential to allow people to live at home for longer. There were financial savings for clients staying at home with the technology compared with the costs of staying in a nursing home: for 10 clients living at home for 2 months, the savings were 23, 665 euro. The study showed that the monitoring system represents a potentially useful early warning system to detect a situation before it requires emergency intervention.